Detection of titin fragments in urine in response to exercise-induced muscle damage. - Kazue Kanda; Jun Sakuma; Takayuki Akimoto; Yasuo Kawakami; Katsuhiko Suzuki (PLoS ONE, 2017)
Many studies have attempted to determine the associations between blood biomarkers and exercise-induced muscle damage. However, poor correlations between the changes in biomarker levels and the magnitude of muscle symptoms have been reported. Recent advances in proteomic tools offer a strategy for the comprehensive analysis of protein expression, which can be used to identify biomarkers. Here, we used a proteomic analysis to identify urinary proteins that appear in response to a calf-raise exercise, including repetitive eccentric muscle contractions, and found that a titin (also known as connectin) N-terminal fragment molecule appears in the urine after eccentric exercise. We measured the titin fragment in urine samples from nine individuals before and after eccentric exercise using a newly-established enzyme-linked immunosorbent assay and found that the titin fragment excretion rate increased 96 h after the exercise (5.1 to 77.6 pg/min, p <0.01). The changes in the titin fragment excretion rate were correlated strongly with blood markers of muscle damage and with muscle symptoms. These findings suggest that the urinary titin fragment is potentially a noninvasive biomarker of muscle damage.